Cost-benefit analysis of the integrated pharmaceutical supply chain information service after the establishment of the Korean Pharmaceutical Information Service - Kim, Myojeong; Lee, GeunWoo; Hwang, Yungi; Kim, Tae Hyun; Kim, Dong-Sook (Frontiers in Pharmacology, 2022)
Background: The Korean Pharmaceutical Information Service (KPIS) was established in October 2007 to increase the transparency of the pharmaceutical supply chain by integrating relevant information. This study aimed to describe the KPIS program and perform a cost-benefit analysis of the KPIS. Methods: We conducted a cost-benefit analysis based on cost savings in terms of National Health Insurance (NHI). The outcome measures were the net financial benefit and benefit-cost ratio over the 12 years since the establishment of the KPIS. The cost estimate included the costs of labor and business operations, the development of an information entry system, and office maintenance. Financial benefits were defined as savings resulting from the implementation of the program based on KPIS data. Social benefits were defined as the prevention of recalled medicines from entering the supply chain and the decrease in inventory and disposal. Results: The KPIS clearly resulted in a net financial benefit, saving 37.2 million USD, which was 2.6 times higher than the cost of implementation. While the benefit-cost ratio was less than 1 during the first period, it exceeded 3.4 during the second period. After calculating and integrating social benefits, the net benefit increased to 571.6 million USD, and the benefit-cost ratio was 24.8. A sensitivity analysis of the annual benefit showed that the net benefit varied from a low of -1.5 million USD to a high of 24.7 million USD according to the program implementation year. Conclusion: The establishment of the KPIS and a system for collecting information on the pharmaceutical supply chain showed meaningful financial and social benefits when compared to the input cost. Since no other countries have an integrated pharmaceutical information system that incorporates all information from production to administration, the example of the KPIS can provide a precedent for other countries.